Sodium p-Toluenesulfinate Enhances the Bonding Durability of Universal Adhesives on Deproteinized Eroded Dentin - Yorichika Shioya (MDPI AG, 2021)
The effects of deproteinization using sodium hypochlorite (NaOCl) and the subsequent application of an antioxidant (sodium p-toluenesulfinate, STS) onto the bonding durability of universal adhesives on eroded dentin were investigated. Untreated sound dentin served as the control, whereas eroded dentin, which had been prepared by pH-cycling in 1% citric acid and a remineralization solution, was either untreated, deproteinized with a 10% NaOCl gel or deproteinized with the 10% NaOCl gel and subsequently treated with an STS-containing agent. The dentin surfaces were bonded using a universal adhesive (Clearfil Universal Bond Quick, Scotchbond Universal or G-Premio Bond), and the micro-tensile bond strength (µTBS) test was performed after 24 h or 10,000 thermal cycles. The µTBS data were statistically analyzed using a three-way ANOVA and Tukey’s HSD post hoc tests. The lowest µTBS was measured on untreated eroded dentin (p < 0.001). Deproteinization of eroded dentin resulted in µTBS similar to untreated sound dentin (p > 0.05), but the highest µTBS was obtained if deproteinization was followed by the application of STS. Thermocycling significantly decreased µTBS in all groups (p < 0.001), except for STS-treated deproteinized eroded dentin (p > 0.05). This indicated that deproteinization, followed by the application of STS, could enhance the bonding durability of universal adhesives on eroded dentin.